2020
DOI: 10.21203/rs.2.21577/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low-arginine and low-protein diets induce hepatic lipid accumulation through different mechanisms in growing rats

Abstract: Background: Dietary protein deficiency and amino acid imbalance cause hepatic fat accumulation. We previously demonstrated that only arginine deficiency or total amino acid deficiency in a diet caused significant hepatic triglyceride (TG) accumulation in young Wistar rats. In this study, we explored the mechanisms of fatty liver formation in these models.Methods: We fed 6-week-old male Wistar rats a control diet (containing an amino acid mixture equivalent to 15% protein), a low-total-amino acid diet (equivale… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…1c,d, Supplementary Table S3). While a ΔArg diet inhibited hepatic TAG secretion, resulting in fatty liver 13 , our results indicated that dietary adenine, but not guanine, fully rescued TAG secretion in the liver (Fig. 1e, f).…”
Section: Adenine Supplementation Restores Tag Secretion In the Liver mentioning
confidence: 59%
See 1 more Smart Citation
“…1c,d, Supplementary Table S3). While a ΔArg diet inhibited hepatic TAG secretion, resulting in fatty liver 13 , our results indicated that dietary adenine, but not guanine, fully rescued TAG secretion in the liver (Fig. 1e, f).…”
Section: Adenine Supplementation Restores Tag Secretion In the Liver mentioning
confidence: 59%
“…A previous study demonstrated that a low-protein/amino acid diet and a low-arginine diet resulted in significant fatty liver development 4,5 , which led to the assumption that dietary arginine intake could have an important role in NAFLD progression. However, dietary arginine intake did not correlate with hepatic TAG levels, and a low-amino acid diet and a low-arginine diet induced fatty liver through a different mechanism, although both diets contained the same amounts of arginine 13 . This suggests that dietary amino acid concentrations are not primarily important; instead, serum amino acids are associated with hepatic lipid metabolism.…”
mentioning
confidence: 81%